STUDY ON FREE VIBRATION OF SKEW PLATE USING FINITE ELEMENT METHOD - Budiman Budiman (University Of Muhammadiyah Jakarta, 2022)
A numerical procedure is presented for free vibration analysis of skew plates using the finite element method. The finite element method is a tool used by many researchers to analyze plates element and gives good results. In this research, the natural frequency of the plate is obtained through free vibration analysis, the analysis utilizes skew plate elements with several skew angles and varying length to thickness ratios. The reference solution in the literature will be used as a comparison to obtain the convergence behavior of the plate element.